Practical concepts and strategies for early diagnosis and management of eosinophilic gastrointestinal disorders in East-Asian children - Byung-Ho Choe (Clinical and Experimental Pediatrics)
Eosinophilic gastrointestinal disorders (EGIDs) are emerging as significant concerns in the Korean pediatric population and transitioning from rare to more commonly diagnosed conditions. This review discusses the increasing prevalence of EGID among children and adolescents and highlights the complexities involved in its diagnosis and management. This review begins with a thorough examination of the diverse clinical presentations of EGIDs in Korean children, with a special focus on common gastrointestinal symptoms such as abdominal pain, diarrhea, and bloody stool. Additionally, we explored extraintestinal manifestations, including growth failure, malnutrition, and associated allergic comorbidities, highlighting their importance in the clinical landscape of EGIDs. Because of its subtle and overlapping symptoms with those of other gastrointestinal disorders, EGID is frequently underdiagnosed. Addressing this challenge requires maintaining a high index of suspicion and employing a comprehensive diagnostic approach to differentiating EGID from functional gastrointestinal disorders and other inflammatory or systemic diseases such as inflammatory bowel disease. The optimal management of EGID requires a collaborative multidisciplinary strategy that includes dietary management, regular monitoring, and tailored medical interventions. This review emphasizes the importance of proactive patient and caregiver education and regular follow-ups to improve long-term outcomes in affected children. Enhanced awareness among healthcare providers and better educational resources for families are critical for the early identification and effective management of EGID among pediatric patients.